The evaluation of the Master in National Security Administration program of the National Defense College of the Philippines - Coronel, Irma C. (Animo Repository, 2021)
The study aimed to conduct a comprehensive evaluation of the Master of National Security Administration (MNSA) Program of the National Defense College of the Philippines for the purpose of determining its performance and impact. To achieve this, a three-part study was designed by way of a Program Evaluation for AY 2020-2021, an Alumni Tracer Study of selected batches of graduates, and an Employer Survey involving superiors and/or immediate supervisors of the MNSA alumni. The study was descriptive in nature. It included seven groups of respondents: (1) 84 MNSA students enrolled at the time of survey (i.e., RC56) who participated in Lecture and Course Evaluation, and Focus Group Discussions (FGD) every term, (2) alumni respondents from batches RC51 to RC55 who responded to the Alumni Tracer Study online form (N=78) and who participated in the FGDs (N=23), (3) four Key Stakeholders from Department of National Defense, Philippine Army, Philippine Navy, and Philippine Air Force who were interviewed individually, (4) nine module directors who participated in the FGDs, (5) nine education specialists/training administrators of the different branches of the military who participated in the FGD, (6) seven staff of the academic division of the NDCP who participated in the FGD, and (7) 16 superiors/immediate supervisors of the MNSA alumni who responded to the Employer Survey form. Various data gathering instruments were employed. Descriptive statistics were used for data analysis. Responses to open- ended questions were analyzed using NVIVO software.